The Effect Credit Restructuring Relaxation on Financial Performance in LPD Buleleng Regency During the Pandemic of Covid-19 - Putu Eka Nopiyani; Ni Made Wulan Sari Sanjaya; Riana Dewi Kartika (International Journal of Social Science and Business, 2021)
During the Covid-19 pandemic, several Village Credit Institutions (LPD) experienced difficulties in their operations, so doing business would need to make various efforts. The implementation of various programs to support policies related to credit is carried out to maintain the growth of Village Credit Institutions (LPD), one of which is the relaxation of credit restructuring policies for people who have credit at Village Credit Institutions (LPD). This study aims to analyze the effect of the relaxation of credit restructuring on LPD financial performance during the Covid-19 pandemic. The nature of this research is an explanation with quantitative methods to test the causality of these variables. The variables in question are the relaxation of credit restructuring and performance. The total population of this study was 81 LPD. Determination of the sample using random sampling technique to obtain a total sample of 46 LPD. This research data collection uses documentation and questionnaire techniques. The data technique used in this study is a simple linear regression with the help of the SPSS 21 application. The results of this study are a positive analysis credit restructuring regression coefficient of 0.968 which means that each increase in credit restructuring by one unit will lead to an increase in the financial performance of 0.968 with the assumption of independent variables other constant. The results of data analysis showed that credit restructuring partially affected financial performance. The key is that credit restructuring has a significant positive effect on the financial performance of the Buleleng Regency LPD during the Covid-19 Pandemic.